EFEKTIVITAS AROMATERAPI GERANIUM TERHADAP INTENSITAS NYERI HAID (DISMENORE) PADA MAHASISWI KEPERAWATAN UNIVERSITAS RIAU - Mala Sasmita; Oswati Hasanah; Yufitriana Amir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Menstruation is bleeding in the uterus that takes place periodically as a result of the endometrium undergoing changes in the hormones estrogen and progesterone. Dysmenorrhea is discomfort during the menstrual cycle experienced by women of childbearing age. Geranium aromatherapy can reduce the degree of pain in women who experience dysmenorrhea. This study aims to determine the effectiveness of geranium aromatherapy on the intensity of menstrual pain in students of collaboration at the University of Riau. The research design used a quasi-experimental design with a pre-test and post-test control group design. The sample used was 40 respondents at the Faculty of Nursing, Riau University, which were taken based on inclusion criteria with purposive sampling technique. The measuring instrument used is an observation sheet using a Numeric rating scale. The analysis used is univariate analysis and bivariate analysis using independent t test and t dependent. The results of univariate analysis showed that the majority of respondents were at the age of 22 years as many as 11 respondents (27.5%). The results of the bivariate analysis in this study showed that the administration of geranium aromatherapy was effective on the intensity of menstrual pain with p value (0.000) < (0.05) and a decrease of 2.25 points after the administration of aromatherapy in the intervention group. It can be concluded that the administration of geranium aromatherapy is effective against the intensity of menstrual pain (dysmenorrhea). This should be a concern for women who experience dysmenorrhea to use geranium aromatherapy as an alternative non-pharmacological treatment and can be practiced independently.Keywords: Dysmenorrhea, female student, geranium aromatherapy